Assessment of Ground Deformation and Landslide Susceptibility Using InSAR and Hypsometric Data in Jayapura City, Papua - Anas, Nur Ayu; Hasudungan, Harsan Ingot; Indrajati, Rahmat; Yonas, Marcelino N.; Hutami, Harnanti Y. (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2025)
Ground deformation and landslides are major geohazards affecting Jayapura City, Papua, due to its active tectonic setting and steep topography. This study aims to assess the correlation between surface deformation and landslide susceptibility using a combination of Interferometric Synthetic Aperture Radar (InSAR) and hypsometric analysis. Sentinel-1A SAR data from ascending and descending tracks, combined with DEMNAS elevation data, were used to detect deformation patterns and evaluate geomorphological maturity through hypsometric parameters. The results reveal significant deformation patterns, including subsidence up to –0.77 m and uplift up to +0.25 m, predominantly concentrated in sub-watersheds Sw2, Sw3, and Sw4. Hypsometric analysis indicates that most sub-watersheds are in the mature geomorphological stage (HI between 0.476 and 0.495), except Sw14, which is classified as young (HI = 0.501). Validation with the landslide inventory further confirms this correlation: 75% of documented landslides occurred in areas of high deformation, while 25% were associated with moderate deformation, and none in low or stable zones. These findings provide essential insights for disaster risk reduction, highlighting priority areas for slope stabilization, land-use management, and early warning systems.